The Man Who Did the Right Thing: A Romance - Johnston, Harry, 1858-1927 (Salt Lake City, UT : Project Gutenberg, 2014)
"The Man Who Did the Right Thing: A Romance" by Sir Harry Johnston is a novel written in the early 20th century. Set in the late 19th century, the story delves into themes of duty, love, and the moral complexities of missionary work. The main characters are Lucy Josling and John Baines, whose engagement unfolds against the backdrop of John's impending departure to Africa as a missionary, an endeavor Lucy grapples with amid her own desires for adventure and her rooted life in England. At the start of the narrative, tension is established surrounding Lucy$1 (Bs betrothed, John, who is preparing to leave for Africa. As John delivers his farewell sermon in their small community, Lucy feels both pride and anxiety over his mission. Their relationship is complicated by the disapproving presence of John's mother and the mundane concerns of village life, while Lucy's internal conflict grows as she contemplates her future and roles both as a wife and a missionary's aide. The opening chapters effectively blend gentle social commentary with romantic anticipation, setting the stage for Lucy's journey of self-discovery and the trials they may face together in their pursuit of faith and fulfillment. (This is an automatically generated summary.)s
Release date is 2014-04-21
Produced by Al Haines
Keywords: Missions -- Tanzania -- Fiction; British -- Africa, East -- Fiction